Habitat maps of two intertidal gleaning areas in Zanzibar, Tanzania, derived from Indo-Pacific Seagrass Network surveys conducted between 29th November - 8th December 2018 - Felicity Pike; Lina Mtwana Nordlund (PANGAEA, 2019)
Ground truthing data taken as part of a habitat mapping survey of Nyamanzi and Unguja Ukuu, Zanzibar (Tanzania), conducted between 29th November -8th December 2018. These two sites are participating sites in the Indo-Pacific Seagrass Network (https://indopacificseagrass.network/), and are being investigated as part of a large-scale data collaboration project on seagrass-associated gleaning in the Indo-Pacific region. Habitat maps derived from this data are intended to demonstrate the distribution of different intertidal habitats within the seascape of study sites. This approach allows a robust ground-truthing method useful in determining the habitat composite of intertidal gleaning areas, and how characteristics of the seascape could potentially facilitate gleaning fisheries. The mapping survey methodology followed the protocol established by the Indo Pacific Seagrass Network (IPSN) and involved in situ assessments, at low tide periods. The observers transpassed the intertidal area on foot to record the habitat type, GPS coordinates and water depth at survey points. Data point sampling was undertaken in a non-random fashion, ensuring that each data point was encompassed by a 5m radius of homogenous habitat. Data points of the same habitat-type were collected a minimum of 50m apart. As this was a seagrass-focused study, the level of coverage for seagrass survey points were additionally recorded, (i.e. sparse, intermediate or dense coverage). Surveys and GPS coordinates were undertaken using an IPSN form on the ODK Collect app.
Supplement to: Pike, F; Nordlund, LM (2019): Indo-Pacific Seagrass Network, 2018. IPSN research protocol: IPSN Habitat Mapping.